A NEW LEGAL SOLUTION ON RECIDIVISM IN SERBIАN CRIMINAL LEGISLATION - Bodrožić, Ivana; Đorđević, Đorđe (NBP. Nauka, bezbednosti, policija, 2021)
From the adoption of the Criminal Code in 2006 until the latest amendments of 2019, the Serbian criminal legislation treated recidivism as an optional aggravating circumstance, which had its specific legal status in comparison with other mitigating and aggravating circumstances. According to the new legal solution, instead of being optional, recidivism has become a mandatory aggravating circumstance, which together with clearly specified conditions for harsher penalties narrows down the possibility of free judicial decision-making when meting out punishment. The paper answers several questions: whether harsher penalties for recidivists are only the result of continuous tightening of repression at a normative level, whether and to what extent the criminal-law framework has been improved, and whether returning to some solutions, which were not normally applied in court practice, can be marked as approriate to achieve the desired degree of crime prevention. Final critical conculusion is that the new legal solution on recidivism appears regressive, given that the court is strictly bound by the law through oblitatory conditions regarding prior and persistent offending, which is in compliance with the general trend of tightening repression at the normative level and reducing the role of the court to the level of administrative application of the norm.